A Modulation Strategy for Suppressing Current Ripple in H7 Current Source Inverters Through Coordinated Switching Operations - Weiqi Wang; Longfei Wei; Xupeng Fang; Xi Liang; Kun Li; Xiaoting Xia (Energies)
The DC bus current ripple is a critical performance parameter affecting the operation of current source inverters (CSIs). In high-power applications, CSIs often operate at lower switching frequencies to minimize losses. However, maintaining low levels of DC bus current ripple necessitates the use of large inductors on the DC side, which increases the size, weight, and cost of the system. This paper first explores the inherent limitations of conventional CSI designs. Subsequently, it proposes a hierarchical coordinated switching modulation strategy based on the H7 current source inverter (H7-CSI) to address the issue of DC bus current ripple. By segmenting the zero-vector states, the proposed method fully utilizes the modulation freedom of the H7-CSI, achieving high-frequency chopping effects on the DC-side current. Experimental results show that the new modulation strategy reduces the amplitude of DC bus current ripple to 43% of that achieved by conventional CSIs under similar switching loss conditions. Furthermore, the dynamic performance of the proposed scheme remains consistent with conventional CSIs. Spectrally, this method exhibits improved performance in the low-frequency range and slightly degraded performance in the high-frequency range, although the latter remains within acceptable limits.